Carta del pe. Juan de habera el qual y el padre Antonio criminal y el padre Niculao Lanciloto fueron los primeros que despues del padre Maestro francisco y Micer Paulo fueron embiados a la Jndia y es pera el padre Martin de Santa Crus que entonces era reitor del collegio de Jhús de Coimbra escrita a 20 de Nouiembre de 1545 años (1545)
This abstract describes a composite historical document comprising multiple interrelated letters and administrative records dating from 1545, originating primarily from Malacca, Zomba, Goa, and the College of Santa Fé—likely situated in Portuguese India or Southeast Asia. The material includes correspondence authored by Jesuit and Augustinian missionaries, notably Fathers João de Gábara, António, Nicolau Lanciloto (also cited as Planaloto), Francisco Sallamo, Francisco de Mancilla, and S. Affonso D’Aveiro, addressed to figures including Father Martinho de Santa Cruz (Rector of the College of Jesus in Coimbra) and Father Comel. Key locations referenced are Malacca, Macassar, Cojon (or Kojoen), Oujo (Ujo), the Cape of Comorim, Goa, Ambueno, and territories associated with the Apostle Saint Thomas. The documents detail missionary activities, catechumenate organisation (*Fianos*, *mocos*), bilingual liturgical practice, translation of Spanish doctrinal works into Indigenous languages, baptismal administration to Muslims (*mouros*) and adherents of Indigenous religions (*gentios*), political tensions surrounding Christian conversion in Cojon—including the martyrdom of Deshoy Fin Cipeg and reported celestial miracles—and logistical arrangements for personnel deployment, supply procurement, and ecclesiastical governance. The collection reflects urgent pastoral needs, inter-order coordination, colonial administrative structures, and early modern Catholic evangelisation strategies across South and Southeast Asia.
Keywords: António; Augustinian Missionaries; Beira, Pe. João da; Bera, Pe. João de; Camerino, Pe. Paulo; Camerte, Pe. Paulo; Coimbra; College of Santa Fé; Criminal, Pe. António; Francis Xavier, Saint; Francisco, Pe. M.; Goa; Habera, Pe. João de; Jesuit Missionaries; João de Gábara; Lanciloto, Pe. Nicolau; Malacca; Martim de Santa Cruz, Pe.; Micer Paulo; Nicolau Lanciloto; Paulo, Pe. Micer; Portuguese India Administrative Records; Transcription; Índia